Role of SPRY4 in health and disease - Pan, Hao; Xu, Renjie; Zhang, Yong (Frontiers in Oncology, 2024)
SPRY4 is a protein encoding gene that belongs to the Spry family. It inhibits the mitogen-activated protein kinase (MAPK) signaling pathway and plays a role in various biological functions under normal and pathological conditions. The SPRY4 protein has a specific structure and interacts with other molecules to regulate cellular behavior. It serves as a negative feedback inhibitor of the receptor protein tyrosine kinases (RTK) signaling pathway and interferes with cell proliferation and migration. SPRY4 also influences inflammation, oxidative stress, and cell apoptosis. In different types of tumors, SPRY4 can act as a tumor suppressor or an oncogene. Its dysregulation is associated with the development and progression of various cancers, including colorectal cancer, glioblastoma, hepatocellular carcinoma, perihilar cholangiocarcinoma, gastric cancer, breast cancer, and lung cancer. SPRY4 is also involved in organ development and is associated with ischemic diseases. Further research is ongoing to understand the expression and function of SPRY4 in specific tumor microenvironments and its potential as a therapeutic target.